Fraser syndrome with extremely rare features of unilateral anophthalmia and penile torsion in an Afghan neonate: A case report - Turyalai Hakimi; Mansoor Aslamzai (Global Pediatrics)
Background: Fraser syndrome is a very rare genetic disorder with multiple organ-system abnormalities. The diagnosis is usually made on the basis of clinical examination, and management requires a multidisciplinary approach. Case Presentation: We present a case of Fraser syndrome with very rare manifestations of unilateral anophthalmia and moderate penile torsion in an Afghan neonate who was born to a 16-year-old mother. Physical findings and a CT scan of the brain and eyes were used to diagnose the aforementioned syndrome. The surgical repairs of cryptophthalmos and penile torsion were planned to be performed after infancy, and the baby was discharged in good health. Conclusion: Anophthalmia and penile torsion are very rare components of Fraser syndrome. Very young maternal age may play a predisposing role in the pathogenesis of Fraser syndrome. The multiple organ defects in Fraser syndrome make this entity more challenging to deal with, particularly in low-resourced settings.